2011
DOI: 10.1021/ja107895g
|View full text |Cite
|
Sign up to set email alerts
|

Computationally Designed and Experimentally Confirmed Diastereoselective Rhodium-Catalyzed Pauson−Khand Reaction at Room Temperature

Abstract: The computational analysis of the rhodium-catalyzed Pauson-Khand reaction indicates that the key transition state is highly charge-polarized, wherein different diastereoisomers have distinctively different charge polarization patterns. Experimental studies demonstrate that chloro-enynes provide the optimal σ-electron-withdrawing group to promote polarization and thereby reduce the activation barrier to provide a highly diastereoselective reaction at room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 24 publications
0
33
0
1
Order By: Relevance
“…15 Although the chemical steps in the catalytic cycle seem identical on first sight, the oxidative addition promoted by the fivecoordinate Rh-complex is fundamentally different from the same reaction mediated by the four-coordinate Rh-analogue. Figure 6 provides an intuitive summary of the diastereoselective metallacarbocycle forming event using the five-coordinate Rhcomplex.…”
Section: ■ Discussionmentioning
confidence: 99%
“…15 Although the chemical steps in the catalytic cycle seem identical on first sight, the oxidative addition promoted by the fivecoordinate Rh-complex is fundamentally different from the same reaction mediated by the four-coordinate Rh-analogue. Figure 6 provides an intuitive summary of the diastereoselective metallacarbocycle forming event using the five-coordinate Rhcomplex.…”
Section: ■ Discussionmentioning
confidence: 99%
“…[4] The calculations predicted that changing the alkyne terminus from H to Cl would significantly lower the barrier to formation of the cis isomer by 4 kcal/mol, but not significantly reduce the barrier to formation of the trans isomer. To verify this, Evans and coworkers treated the corresponding enynes with a rhodium catalyst at room temperature (Scheme 1) and observed no reaction when the alkyne was terminal, but were able to isolate the cyclopentenone in 74% yield when substituted with chlorine.…”
Section: Achiral/racemic Processesmentioning
confidence: 99%
“…In a joint effort between the Baik and Evans groups, factors controlling the diastereoselectivity of rhodium-catalyzed Pauson-Khand reactions (Scheme 7) were discovered. [17] This understanding was parlayed into the design of new substrates predicted to undergo highly diastereoselective Pauson-Khand reactions. Quantum chemical calculations on rate-determining transition state structures leading to the major and minor products suggested that both structures are polarized, but in opposite directions.…”
Section: Predicting the Diastereoselectivity For An Organometallic Rementioning
confidence: 99%